Rancang Bangun Sistem Manajemen Jadwal Pelajaran Berbasis Mobile Menggunakan Flutter dan Node.js dengan Fitur Push Notification - Ja'far Ja'far; Wahyu Sri Utami (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of information technology encourages educational institutions to undertake digital transformation in data management and academic services, particularly in the lesson scheduling system. At Muhammadiyah Mlonggo Junior High School in Jepara, the learning schedule design stage still relies on conventional methods involving bulletin boards and printed files. This method causes various problems, including delays in information dissemination, a high potential for data errors, and the absence of a centralized mechanism to maintain schedule consistency and accuracy. Schedule design problems have a direct impact on the effectiveness of teaching and learning activities for both teachers and students. This study aims to design and implement a mobile-based lesson schedule application using Flutter and Node.js equipped with an automatic push notification feature to improve the efficiency, accuracy, and timeliness of school schedule management. The software development method used is the Waterfall model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The backend system was developed using a Node.js/Express-based RESTful API with a MySQL database to ensure data integrity and consistency. This application is equipped with a data validation mechanism and schedule conflict detection to prevent time conflicts during the input and update process of the schedule, so that information accuracy can be maintained. Functional testing was conducted using the Blackbox Testing method on all the main features of the application. The findings of the research results show that the application is able to present lesson schedules in real-time, simplify the process of updating information, and provide notifications to teachers and students as reminders of teaching and learning activities. The test results show that 100% of the functions run according to the established specifications. Thus, this application can improve efficiency, accuracy, and effectiveness in managing lesson schedules in the school environment. Overall, the application is able to present lesson schedules in real-time, speed up the process of updating information, and provide reminder notifications to teachers and students, thus supporting more effective and reliable management of learning schedules in the school environment.